If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(2n + -7) = 4 + -3n Reorder the terms: 6 + -1(-7 + 2n) = 4 + -3n 6 + (-7 * -1 + 2n * -1) = 4 + -3n 6 + (7 + -2n) = 4 + -3n Combine like terms: 6 + 7 = 13 13 + -2n = 4 + -3n Solving 13 + -2n = 4 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 13 + -2n + 3n = 4 + -3n + 3n Combine like terms: -2n + 3n = 1n 13 + 1n = 4 + -3n + 3n Combine like terms: -3n + 3n = 0 13 + 1n = 4 + 0 13 + 1n = 4 Add '-13' to each side of the equation. 13 + -13 + 1n = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1n = 4 + -13 1n = 4 + -13 Combine like terms: 4 + -13 = -9 1n = -9 Divide each side by '1'. n = -9 Simplifying n = -9
| 9+2x=3x-7 | | -7x+3=2x+2 | | 11x+3y=56 | | -9(5)+125= | | 15x-28y=32 | | (4x-5y)(16x^2+kxy+25y^2)k= | | 2000-25p=1715+70p | | D^3=125 | | (p^-5/4p^-1)^3 | | -0.444444444=-4/9 | | -0.444444444= | | i^155= | | 7y+5=8y-4 | | 3x^3+3x^2-126x=0 | | 12-1/3x=8 | | 3x^3+3x^2-126=0 | | (2y+4)+(5b+1)= | | ln(x)=ln(x-8)+ln(3) | | 5e^6x=8e^8x | | (9-x)(3x+7)=0 | | (4/9)-(2/3) | | (8x-12)+(5x-3)= | | x-13=102 | | x-2=113 | | 2(7x-3x)=35+5x | | 51=4v+11 | | 16x+y=30 | | 3(5)+2=x | | x^2-20x+130=0 | | (x-3)2+(y-5)2=20 | | 15x+x+y=30 | | 4u+11=26 |